"A Willingness to Put a Knife in Its Own Back": Advertising, Self-Censorship, and the Weekly Mail's Resistance in Apartheid South Africa. Issue 2 (3rd April 2017) - Trabold, Bryan
ABSTRACT: The need for newspapers to obtain advertising revenue can create significant pressures to engage in self-censorship. The Weekly Mail in apartheid South Africa, in addition to contending with the extensive system of censorship created by the government, also had to contend with the challenge of obtaining revenue without compromising its core journalistic principles. Based on interviews conducted with the editors and journalists at this newspaper, as well as an examination of every edition between 1985‒1990, I examine the innovative ways in which those who worked for this newspaper were able to read the complex economic and political dynamics, domestically and internationally, in order to obtain the necessary revenue to survive. Moreover, extensive evidence reveals that those at the Weekly Mail obtained this revenue without engaging in self-censorship. This case study of the Weekly Mail not only highlights a compelling story of anti-apartheid resistance but also has implications for journalists in other countries who face similar pressures due to financial constraints.